The symbolism of color and dreams in the Injinash’s “Blue Sutra” (Koke sudur) - V. Yangindulam (Nomadic Civilization: Historical Research)
The great writer V. Injannashi used the colour, light, and dream as symbols to express the harmonic roles in his novel «Khukh sudar». Its worldview and philosophy are inextricably linked to the attitude of the society at the time. Injannashi used a wide range of ﬁgurative techniques, including metaphors, diminutives, vintage words, carousels, allegories, and symbols, which are related to traditional concepts of eastern artistic thought. The winning and the rising events, the power of the hero were expressed through white light, red light when the bad events and the losing events were described by black anger, foggy darkness. The dream is described 22 times in the novel. Most of the dreams are the symbol of troubles that may happen in the future. There are lots of events that are dependent on dreams.